A reduction in triclosan and triclocarban in water resource recovery facilities' influent, effluent, and biosolids following the U.S. Food and Drug Administration's 2013 proposed rulemaking on antibacterial products - Brose, Dominic A (Water environment research : a research publication of the Water Environment Federation, 2019)
© 2019 Water Environment Federation.